The Impact of Digitalization on MSMEs’ Financial Performance: The Mediating Role of Dynamic Capability - Maya Indriastuti; Indri Kartika (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThe COVID-19 pandemic has negatively affected the 82.9% of MSMEs. They experienced a significant decrease in operating profit due to fixed production costs or increased production costs while the sales declined. Therefore, it requires various strategies to boost the financial performance of MSMEs through digitalization and dynamic capability. The sample consisted of 282 respondents from MSMEs in Central Java which then all primary data were processed using structural equation model analysis. The results of the study showed that digitalization and dynamic capability could enhance the MSMEs' financial performanceand the variable of dynamic capability succeeded in mediating the effect of digitalization on the MSMEs' financial performance. Keywords:digitalization, dynamic capability, MSMEs' financial performance Dampak Digitalisasi Terhadap Kinerja Keuangan UMKM: Peran Mediasi Kemampuan Dinamis AbstrakPandemi COVID-19 telah menyebabkan 82,9% UMKM mengalami dampak negatif yakni penurunan profit usahasecara signifikan akibat biaya produksi tetap atau bahkan meningkat sementara penjualan menurun. Oleh karena itu di butuhkan berbagai strategi untuk mendongkrak kinerja keuangan UMKM melalui digitalization dan dynamic capability. Sampel penelitian ini sebanyak 282 responden dari UMKM di Jawa Tengah yang kemudian semua data primer diolah menggunakan analisis Structural Equation Modeling. Hasil penelitian menunjukkan bahwa variabel digitalizationdan dynamic capability mampu meningkatkan kinerja keuangan UMKM serta variabel dynamic capability berhasil memediasi pengaruh digitalization dengan kinerja keuangan UMKM. Kata kunci:digitalization, dynamic capability, kinerja keuangan UMKM